Discovery of fructans in Archaea - TOKSOY ÖNER, EBRU (ELSEVIER SCI LTD, 2019)
Fructans are fructose-based oligo-and polysaccharides derived from sucrose that occur in a plethora of Eubacteria and plants. While fructan-producing (fructanogenic) Eubacteria are abundant in hypersaline environments, fructan production by Archaea has never been reported before. Exopolysaccharides accumulated by various Archaea from the Halobacteria class (belonging to the genera of Halomicrobium, Haloferax and Natronococcus) originating from different locations on Earth were structurally characterized as either levans or inulins with varying branching degrees (10%-16%). Thus, we show for the first time in the literature that fructans are produced in all three domains of life, including Archaea. This proof of concept will not only provide insight into Archaeal glycans and evolution but it may also open new frontiers for innovative strategies to overcome the ever-increasing threat of excessive salinization.
Keywords: Fructan; Archaea; Halophiles; Salinity; Inulin; Levan; HUMAN GUT; SP-NOV.; STARCH; LEVAN; SPECTROSCOPY; HALOARCULA; MUKOHATAEI; BACTERIA